The Influence of Profit Management on The Financial Performance of Initial Public Offering Companies Listed on The Indonesian Stock Exchange, 2010-2018 - Wirawan, Richard Tjipto; Basana, Sautma Ronni (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2025)
This research aims to determine the effect of earnings management on the financial performance of Initial Public Offering companies listed on the Indonesia Stock Exchange in 2010 - 2018. This research also uses two control variables: firm size and sales growth. The sample used is non-financial companies that report complete financial reports. The method used for this research is Ordinary Least Square regression with the Pooled Least Square data type. The results of this research indicate that earnings management has a significant negative effect on the company's financial performance. The regression results also explain that firm size has a significant positive result, which means that the impact of earnings management on the company's financial performance also depends on the size of the company. However, the control variable sales growth does not have significant results, so the impact of earnings management on the company's financial performance does not depend on the company's sales growth.